The Datafication of Newsrooms: A Study on Data Journalism Practices in a British Newspaper - Ahmet Buğra Kalender (Journalism and Media, 2024)
This study investigates the function of data journalism in a UK newsroom using Bourdieu’s field theory. The collection of study data was conducted through in-depth interviews, utilising a qualitative research methodology. The data obtained revealed that data journalism, a sub-field of journalism, continues to develop in an interdisciplinary structure and creates a new type of habitus (data habitus) within the field of journalism. This study also shows that the data journalism team in the newspaper has moved from being niche to being established as one of the most active and effective main sections of the newsroom, and that data-driven journalism has the potential to influence other teams. Lastly, this study suggested that the newsroom is undergoing a process of datafication by indicating the newspaper’s intention to develop data skills beyond the data journalism team.